The Mass Spectrum of Elementary Particles in Unitary Quantum Theory and Standard Model (Global Journal of Science Frontier Research, 2016)
Abstract not found
Keywords: unitary quantum theory; mass spectrum of elementary particles; standard model; wave packet; string theory; supersymmetry